Smart Grid Research and Educational Kit to Enable the Control of Power Electronic-based Systems from Simulations to Experiments in Hours. Issue 2 (2020) - Zhong, Qing-Chang; Wang, Yeqin; Amin, Mohammad; Dong, Yiting; Ren, Beibei
Abstract: Control and power electronics are two major enablers for the paradigm shift of power systems from centralized generation to distributed generation, the electrification of transportation, and the transformation of billions of lives in third-world countries. Experimental validations of control algorithms for these systems play a vital role. However, setting up a suitable experimental system requires time, effort, and a broad range of expertise. This demonstration session aims to help researchers, graduate students, and engineers remove the barriers to go real from simulations to experiments for various power electronic-based systems. It shows that it is possible to obtain experimental results within hours after completing simulations by adopting the SYNDEM Smart Grid Research and Educational Kit, which is a reconfigurable, open-source, multifunctional power electronic converter with the capability of directly downloading codes from Matlab/Simulink. This will maximize the strengths of the control community in developing control algorithms, minimize the efforts on developing hardware systems and programming control algorithms, and improve the efficiency and productivity of research and learning.